Diagnostic Performance of Six Tests for Helicobacter pylori Infection in Peptic Ulcer Bleeding: A Prospective Head-to-Head Comparison - Tanawat Geeratragool; Thanapat Atthakitmongkol; Supathep Tansirichaiya; Pubet Weeranawin; Somchai Leelakusolvong; Monthira Maneerattanaporn (Clinical and Translational Gastroenterology, 2026)
Background: Rapid urease test (RUT) is widely used for diagnosing Helicobacter pylori (HP) because it is inexpensive and practical. However, its accuracy is reduced in peptic ulcer bleeding (PUB). We prospectively performed a head-to-head comparison of diagnostic tests in the same patients to evaluate their performance in this setting. Methods: After endoscopic hemostasis, gastric biopsies were obtained for RUT, histology, and PCR. Blood samples were collected for current infection marker (CIM) and anti-urease antibody. Urea breath testing (UBT) was performed in patients with negative RUT and histology. Diagnostic performance was assessed using a composite reference standard defined by at least 2 positive results among RUT, histology, PCR, and UBT. Logistic regression was used to identify factors associated with false-negative RUT. Results: A total of 135 patients with PUB were enrolled, of whom 36 (27.7%) were HP-positive. Sensitivity/specificity were 69.4%/97.0% for RUT, 55.6%/96.0% for histology, 97.2%/92.9% for PCR, 77.8%/77.8% for CIM, and 83.3%/62.6% for anti-urease antibody. Combining RUT, histology, and either PCR or UBT increased sensitivity to 100% and significantly outperformed RUT alone (P=0.021 and P=0.001, respectively). PCR reduced idiopathic ulcers from 31.9% to 26.7%. Only 43 of 98 patients with negative RUT and histology underwent UBT because of clinical constraints, limiting its practicality despite excellent performance. No predictors of false-negative RUT were identified. Conclusions: In PUB, tissue PCR showed the best overall diagnostic performance among the single tests. RUT alone is insufficient for diagnosing HP, whereas combined testing with RUT, histology, and PCR or UBT achieved the highest diagnostic performance.